6x-1=4-7

Simple and best practice solution for 6x-1=4-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-1=4-7 equation:


Simplifying
6x + -1 = 4 + -7

Reorder the terms:
-1 + 6x = 4 + -7

Combine like terms: 4 + -7 = -3
-1 + 6x = -3

Solving
-1 + 6x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 6x = -3 + 1

Combine like terms: -1 + 1 = 0
0 + 6x = -3 + 1
6x = -3 + 1

Combine like terms: -3 + 1 = -2
6x = -2

Divide each side by '6'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 2x+4=10x-60 | | 64x-10=49x-3x | | 2z-5=4x+2 | | m/5-12=18 | | 3x^2-2x+7=18x^2-12x+63 | | 10=k-20 | | 18x-4=3-11 | | 6.9=-6+x | | 6xy^4/14y | | 64-10=49-3x | | (2/3h)-9=6-(2/3h) | | B=w(5p-2h) | | X^4+2x^3+x^2+32x-240=0 | | P=w(5b-2h) | | 5x-1/4 | | 18x^2-12x=-63 | | 25j=450 | | 100=0.70X | | 5(3)2= | | 7ax-10=5ax+8 | | 49=0.67X | | (-5x)(-6x^5)= | | 100=0.67X | | 2(6x-2)=92 | | 6x+5+4x=25 | | 5(1+4n)=145 | | 100=0.6666X | | 16-14q+19q-7= | | 2+5(x-4)=8-3(x-9)+6x | | 32+x+x=90 | | 55555555555=0 | | 5y-10=12 |

Equations solver categories